The Influence of Pores on Irradiation Property of Selected Nuclear Graphites - Zhengcao Li; Dongyue Chen; Xiaogang Fu; Wei Miao; Zhengjun Zhang (Advances in Materials Science and Engineering)
As structural material and moderator in high temperature gas-cooled reactor (HTGR), nuclear graphite endures large flux of irradiation in its service time. The microstructure of nuclear graphite is a topical issue studied to predict the irradiation property of graphite and improve manufacturing process. In our present work, the pores in graphite are focused, and the relationship between pore and irradiation behavior is discussed. Three kinds of nuclear graphite (IG-11, NBG-18, and HSM-SC) are concerned, and their porosity, pore size, and morphology before and after irradiation are studied, respectively. A comparison between the three graphites shows that dense small pores which are uniformly distributed in graphite bring better irradiation property because the pores can accommodate some of the internal stress caused by irradiation expansion. Coke particles of small size and a thorough mixture between coke and binder are suggested to obtain such pores in nuclear graphite and thus improve irradiation property.